Numerical simulation of slag movement from Marangoni flow for GMAW with computational fluid dynamics. (June 2021) - Cho, Dae-Won; Park, Yeong-Do; Cheepu, Muralimohan
Abstract: This study analyzed the behavior of molten slag, which is an oxide generated during spray mode gas metal arc welding, with computational fluid dynamics. The molten slag, composed mainly of silicate (SiO2 ), is located on the molten pool surface. It is generally assumed that the molten slag is generated around the arc plasma boundary. Therefore, in the numerical simulation in this study the slag is modeled as a spherical particle, which has a specific density and size. To compare the Marangoni flow effect, this study investigated two different cases where the surface tension gradients were different (positive and negative). In both the numerical simulation and experimental results it was found that negative surface tension gradient formed trapped slag on the bead edge while the positive surface tension gradient formed trapped slag on the center of the top surface.